2018
DOI: 10.1002/ejlt.201700500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium Content and Homogenization Method on the Microstructure, Rheology, and Stability of Emulsions Prepared with Soybean Flour Dispersions

Abstract: The objective is to study the microstructure, rheology, and quiescent stability of oil‐in‐water emulsions prepared with defatted soybean flour dispersions, analyzing the effects of calcium concentration and homogenization method. Dispersions are prepared without or with addition of calcium chloride at different concentrations (30, 60, and 90 mg Ca 100 g−1) and treated by heating (100 °C, 40 min) and high‐pressure homogenization (HPH) at 120 MPa. Emulsions are prepared with homogenized dispersions and sunflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The profiles of Monascus pigment double emulsions with 20 and 50 mM Ca 2+ were quite similar. This result can be explained by the binding of SPI by Ca 2+ , leading to the aggregation by electrostatic screening ( 41 ). It was reported that Ca 2+ not only contributed its nutritional property but also acted functionally by allowing the obtaining of double-emulsion systems with creamy texture without the need of addition of saturated fats.…”
Section: Resultsmentioning
confidence: 99%
“…The profiles of Monascus pigment double emulsions with 20 and 50 mM Ca 2+ were quite similar. This result can be explained by the binding of SPI by Ca 2+ , leading to the aggregation by electrostatic screening ( 41 ). It was reported that Ca 2+ not only contributed its nutritional property but also acted functionally by allowing the obtaining of double-emulsion systems with creamy texture without the need of addition of saturated fats.…”
Section: Resultsmentioning
confidence: 99%
“…Plant protein‐coated oil droplets may also be influenced by binding to mineral ions in the aqueous phase. For instance, the binding of cationic calcium ions to the surfaces of anionic proteins or protein‐coated oil droplets can reduce the electrostatic repulsion between them, thereby promoting their aggregation (Marquez, Wagner, & Palazolo, 2018). Thus, elucidating, understanding, and controlling the binding interactions in these kinds of products is critical.…”
Section: Ingredient Functionalitymentioning
confidence: 99%
“…also found that the high shear forces generated by high pressure homogenization resulted in a decrease in particle size of soy protein isolate and zein. Protein particle size increased significantly at higher HSH speeds, which might be due to the aggregation of protein molecules . In general, higher electrostatic repulsion indicates that protein molecules are less prone to aggregation, whereas higher hydrophobic forces result in the aggregation of proteins.…”
Section: Resultsmentioning
confidence: 96%
“…Protein particle size increased significantly at higher HSH speeds, which might be due to the aggregation of protein molecules. 41 In general, higher electrostatic repulsion indicates that protein molecules are less prone to aggregation, whereas higher hydrophobic forces result in the aggregation of proteins. When the HSH speed exceeded 14 500 rpm, the absolute value of the zeta potential and the surface hydrophobicity wileyonlinelibrary.com/jsfa Table 3.…”
Section: Tertiary and Quaternary Structurementioning
confidence: 99%